Homologous series of LC acrylic monomers based on phenyl benzoate core group: synthesis and characterisation. Issue 10 (8th August 2020) - Romero-Hasler, P.; Arismendi, D.; Richter, P.; Soto-Bustamante, E. A.
ABSTRACT: The synthesis and phase characterisation of a homologous series of monomers of acrylic phenyl benzoates has been carried out. The characterisation comprises polarised optical microscopy, differential scanning calorimetry and powder x-ray diffractometry. All monomers are mesogenic, exhibiting either nematic and/or smectic phase. Shorter monomers are nematogenic while longer monomers show a more smectogenic character. Most of the monomers show monotropic phases. Graphical abstract: uf0001